Terms Expressing Spatial Divisions in Old Armenian - Abajyan, Anna; Yuzbashyan, Anahit (Bulletin of Yerevan University B: Philology, 2023)
Grabar's vocabulary has been thoroughly and deeply investigated, but its terminological system which is its constituent part has not been completely analyzed yet. For this reason the examination of the terminological system of Old Armenian is very important and up-to-date. Old Armenian’s terminological system is multi-layered; each sub-layer has its own characteristics at the lexical, morphological and syntactic levels. The source of the term system of Modern Eastern Armenian is the term system of Old Armenian. Accordingly, it is important to examine Old Armenian word-forms and terms from both synchronic and diachronic points of view. Old Armenian literature provides rich factual material for their semantic- etymological study. In particular, the historiography presents the foreign and domestic policy, the spiritual and cultural life of the kings. Each layer of the terminological system with its sub-layers is important with by its internal coordination. Their functional frequency varies depending on their purpose and content. The given study is dedicated to the synchronic investigation of word-terms and terms expressing territorial divisions from the semantic-etymological point of view. We made the original documentation according to Yeghishe's works "About Vardan and the Armenian War" and Pavstos Buzand's "Buzandaran History". Among the spatial divisions, the terms showing political content are of political significance, for example, the world of the Greek people, Country of Armenians, of the border of the country of Armenians, etc. We considered the word-terms of general spatial content units expressing social divisions, such as: source, sea, island, river, etc. According to the semantic-etymological examination carried out by us, 4 of the presented 30 terms are borrowed from Assyrian, 6 from Pahlavi, 1 from Acadian, and the rest are native words.
Keywords: country; world; province; state; border; land; island; sea; burg; glade